Profil Hj. Hastinah Amir: Perempuan Sang Pengabdi Untuk Rakyat dan Daerah - Ashari, Ashari (Rayhan Intermedia, 2025)
Women in their role, not only in the domestic area, but also urgent subjects in performing strategic roles in the public world. The presence of women in the public arena is not merely as ‘followers, complements, or enjoyers’, but they are ‘leaders, actors, and producers’ of development. This research is a socio-historical literature review, with full reference to the results of the researcher's research. The results of the study show that Hj Hastinah Amir is a servant of the people and the region, whose work is deeply rooted in society. Hastinah has a background as an educator, and later became a member of the Pangkep Regency DPRD. The idea is to fight for gender equality, development in various fields of life, economy, politics, law and culture. The description of Hj. Hastina Amir's work becomes a ‘spirit’ in life, especially for regional women.